Editorial - Martins, Lauber (Revista de Engenharia Térmica, 2023)
The editorial of Thermal Engineering of this issue continues the discussion on scientific research needs in vital areas in which thermal engineering has important participation. The main goal is to motivate the readers, within their specialties, to identify possible subjects for their future research. Our modern life would not be possible without electricity and the fuels used in transportation and equipment that bring the so appreciated comfort to the sociedy. Energy is crucial for the development and progress of nations to the point where the level of development of a country is estimated qualitatively by its energy consumption. In these contexts, along with the threat of lack of fossil fuel for the future and the worldwide debate about environemntal impacts, humanity is presented the hard question about how to generate clean energy in a sustainable way facing the estimation that by 2050 the demand of energy will double the demand of the beginning of the century. Oil is the most used fuel nowadays. Its excessive use, however, can birng consequences as for example, its complete depletion and the negative environmental impacts due to the gases generated by its combustion. The International Panel on Climate Change (IPCC) established the goal of stabilizing the level of CO2 concentration below 500 ppm and to limit the increase of the global temperature to 2oC above the pre-industial levels. Taking into consideration the increase need of energy and the relevany of environamental impact matters, renewable energy has been considered an attractive option. It replaces fossil fuels and the tehcnology used for its generation has been substantilly improved in years. Among the most viable sources of renewable energy (solar, wind, thermal, nuclear), bionergy is the one that has the possibility to use the big spetrum of organic substacts (including toxic waste) while at the same time fixes the carbon. Algae is one of those examples. A large range of biofuels as for example, biogas, biohydrogen, biomehtane, biodiesel, bioethanol and biocoal, can be obtained from algae biomass. The mission of Thermal Engineering is to document the scientific progress in areas related to thermal engineering (e.g., energy, oil and renewable fuels). We are confident that we will continue to receive articles’ submissions that contribute to the progress of science.